Modelling and simulation of scattering parameter model for cable joint in a cable system - Mohd Amjad Ridzuan bin Radhi (2023)
Modelling and simulating for underground cable joints are becoming essential for applying non-destructive cable diagnostic techniques to be able to forecast the cable systme condition and measuring the relliability of the system. Modelling of a cable joint to apply cable diagnotic techniques may differ in the use different parameters tp diagnose the different condition of a cable system.